2018
DOI: 10.1002/adfm.201807419
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Organic Precursor–Derived Mesoporous Carbon Spheres with Homogeneously Distributed Molybdenum Carbide/Nitride Nanoparticles for Efficient Hydrogen Evolution in Alkaline Media

Abstract: The generation of hydrogen through water electrolysis is considered as a sustainable approach for future fuel production. Molybdenum (Mo)-based compounds are reported as highly active and inexpensive alternatives to platinum-based electrocatalysts for the hydrogen evolution reaction (HER). Currently, the major challenge for Mo-based HER electrocatalysts lies in establishing new concepts of micro-/nanostructure design to enhance the hydrogen evolution kinetics and realizing facile, large-scale, and green fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
80
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 53 publications
1
80
0
2
Order By: Relevance
“…Recently, metal–organic frameworks (MOFs) have been demonstrated as a new class of multifunctional nanomaterials or precursors for applications in a wide range of fields . Besides utilizing the MOFs directly to serve as nanocarriers or biocatalysts for biomedical applications, MOF‐derived nanocarbons have also presented intriguing physical and chemical properties, such as high photothermal conversion efficiency, facile doping of metal atoms, and large surface area with porous structures …”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal–organic frameworks (MOFs) have been demonstrated as a new class of multifunctional nanomaterials or precursors for applications in a wide range of fields . Besides utilizing the MOFs directly to serve as nanocarriers or biocatalysts for biomedical applications, MOF‐derived nanocarbons have also presented intriguing physical and chemical properties, such as high photothermal conversion efficiency, facile doping of metal atoms, and large surface area with porous structures …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Recently, earth-abundant transition metal carbides such as iron carbide, 6 nickel carbide, 7 tungsten carbide 8,9 and particularly molybdenum carbide (Mo 2 C) [10][11][12][13] have emerged as potential substitutes for precious metal-based materials as HER electrocatalysts. It was found that the HER activity of Mo 2 C materials can be signicantly improved by fabrication of Mo 2 Cbased heterostructures such as Mo 2 N-Mo 2 C, 14,15 MoC-Mo 2 C, 16 Ni/Mo 2 C-PC, 17 NiMo 2 C/NF, 18 Mo x C/Ni, 19 nw-W 4 Mo, 20 and others. [21][22][23][24][25][26] The high activity of these heterostructures derives from synergistic electron transfer and mass transfer phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The rare storage and high cost of these materials severely restrict their practical applications. Therefore, non-noble metal-based materials with high capacitance and low activation energy for energy storage and renewable energy are profoundly needed to replace noble metal materials [7][8][9]. Moreover, developing a material with both energy storage and conversion could not only save the cost but also facilitate its integration.…”
Section: Introductionmentioning
confidence: 99%